Factors Shaping Commitment and Resource Allocation in Managing Quality Tourism Destinations - Dewi, Ike Janita; Ginting, Ginta (Lasigo Akademia Indonesia, 2023)
The research aims at analyzing factors affecting the implementation of the quality tourism paradigm by tourism villages. A tourism village is a community-based tourism which offers a rural tourism experience. The research was carried out in the context of strategy formulation post-COVID-19 pandemic. The research specifically portrays the shifting paradigm from quantity to quality tourism development which takes place partly in response to the pandemic. There are concepts and theories taken from the marketing and human resource management, that is, the branding concept, the Theory of Reasoned Action, and the commitment theory to enrich tourism study. The research is quantitative-causal research. This study selected the research locus in the three tourism villages in the Special Region of Yogyakarta, Indonesia. Data was collected through a survey. Data were analyzed using Structural Equation Modelling. The results of this study show that: 1) Level of awareness, Perceived importance, and Influence of other stakeholders positively affect commitment. 2) Level of awareness and Perceived importance positively affect Resource allocation, 3) Influence of other stakeholders has no effect on Resource allocation, and 4) Commitment positively affects Resource allocation. The research results lead to strategies for managing community-based tourism destinations to offer a quality tourism experience.